Comparative Analysis of Ayurvedic and Allopathic Medicine Preferences Among Bachelor’s Level Students - Raikhola, Pushkar Singh (Nepal Journal of Multidisciplinary Research, 2025)
Background: The coexistence of Ayurvedic and allopathic systems of medicine reflects a growing trend toward integrating traditional and modern healthcare approaches. While Ayurveda emphasizes natural healing and holistic well-being, allopathic medicine is often preferred for its efficacy in treating acute conditions. Understanding healthcare preferences among young adults, particularly Bachelor Running students aged 18-25, is crucial for designing effective healthcare strategies that cater to their unique needs. Objective: This study aimed to assess preferences for Ayurvedic and allopathic systems among Bachelor Running students, focusing on common health issues such as minor injuries, common colds, fever, headaches, and diarrhea. The study also explored the influence of gender and marital status on these preferences. Method: A cross-sectional survey was conducted among 200 Bachelor Running students aged 18-25 from Baneshwor Multiple Campus, Kathmandu, Nepal. Data were collected using a structured questionnaire that assessed preferences for Ayurvedic and allopathic systems for five common health issues, along with demographic information. Descriptive statistics and Chi-Square tests were used to analyze the data. Findings: The results revealed significant gender-based differences in preferences for treating common colds (p = 0.022) and fever (p = 0.037), with one gender more likely to favor Ayurvedic or allopathic systems than the other. However, gender did not significantly influence preferences for minor injuries, headaches, or diarrhea. Marital status showed no significant association with preferences for any of the health conditions examined. Conclusion: The study highlights the importance of considering gender-specific factors when designing healthcare interventions, as gender significantly influences preferences for treating common colds and fever. Preferences for other health conditions are likely shaped by cultural beliefs, accessibility, and prior experiences rather than demographic variables. These findings underscore the need for a balanced approach that integrates traditional and modern healthcare systems to meet the diverse needs of young adults. Novelty: This study contributes to the limited literature on healthcare preferences among young adults, particularly in the context of Ayurvedic and allopathic systems. It provides new insights into the role of gender in shaping preferences for common health issues and highlights the need for further research on other potential determinants of healthcare decision-making.